Healthcare professional views about a prehospital redirection pathway for stroke thrombectomy: a multiphase deductive qualitative study - Day, J; Simmonds, RL; Shaw, L; Price, CI; McClelland, G; Ford, GA; James, M; White, P; Stein, K; Pope, C (BMJ Publishing Group, 2024)
Background: Mechanical thrombectomy for stroke is highly effective but time-critical. Delays are common because many patients require transfer between local hospitals and regional centres. A two-stage prehospital redirection pathway consisting of a simple ambulance screen followed by regional centre assessment to select patients for direct admission could optimise access. However, implementation might be challenged by the limited number of thrombectomy providers, a lack of prehospital diagnostic tests for selecting patients and whether finite resources can accommodate longer ambulance journeys plus greater central admissions. We undertook a three-phase, multiregional, qualitative study to obtain health professional views on the acceptability and feasibility of a new pathway. Methods: Online focus groups/semistructured interviews were undertaken designed to capture important contextual influences. We purposively sampled NHS staff in four regions of England. Anonymised interview transcripts underwent deductive thematic analysis guided by the NASSS (Non-adoption, Abandonment and Challenges to Scale-up, Spread and Sustainability, Implementation) Implementation Science framework. Results: Twenty-eight staff participated in 4 focus groups, 2 group interviews and 18 individual interviews across 4 Ambulance Trusts, 5 Hospital Trusts and 3 Integrated Stroke Delivery Networks (ISDNs). Five deductive themes were identified: (1) (suspected) stroke as a condition, (2) the pathway change, (3) the value participants placed on the proposed pathway, (4) the possible impact on NHS organisations/adopter systems and (5) the wider healthcare context. Participants perceived suspected stroke as a complex scenario. Most viewed the proposed new thrombectomy pathway as beneficial but potentially challenging to implement. Organisational concerns included staff shortages, increased workflow and bed capacity. Participants also reported wider socioeconomic issues impacting on their services contributing to concerns around the future implementation. Conclusions: Positive views from health professionals were expressed about the concept of a proposed pathway while raising key content and implementation challenges and useful ‘real-world’ issues for consideration.